2022
DOI: 10.3390/jpm12030455
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Enabled Electrocardiography Predicts Left Ventricular Dysfunction and Future Cardiovascular Outcomes: A Retrospective Analysis

Abstract: The ejection fraction (EF) provides critical information about heart failure (HF) and its management. Electrocardiography (ECG) is a noninvasive screening tool for cardiac electrophysiological activities that has been used to detect patients with low EF based on a deep learning model (DLM) trained via large amounts of data. However, no studies have widely investigated its clinical impacts. OBJECTIVE: This study developed a DLM to estimate EF via ECG (ECG-EF). We further investigated the relationship between EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Attia et al [12] from the Mayo Clinic created an algorithm that was tested in eight studies [12][13][14][15][16][17], one group from Seoul (the republic of Korea) developed and tested their algorithms in two studies [18,19]. Five research groups (Sbrollini et al) developed in-house algorithms and tested them in separate studies [20][21][22][23][24]. A detailed overview of each study population and outcome can be found in "Supplementary results" (Supplementary Appendix 3), where details are provided for AUC, type of outcome, model adjustments and comparison to other test (e.g., BNP/NT-proBNP).…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Attia et al [12] from the Mayo Clinic created an algorithm that was tested in eight studies [12][13][14][15][16][17], one group from Seoul (the republic of Korea) developed and tested their algorithms in two studies [18,19]. Five research groups (Sbrollini et al) developed in-house algorithms and tested them in separate studies [20][21][22][23][24]. A detailed overview of each study population and outcome can be found in "Supplementary results" (Supplementary Appendix 3), where details are provided for AUC, type of outcome, model adjustments and comparison to other test (e.g., BNP/NT-proBNP).…”
Section: Overviewmentioning
confidence: 99%
“…A retrospective design was used in eleven studies [12][13][14][17][18][19][20][21][22][23][24], one was a case series [15] and three were prospective cohort studies [16,25,26]. Apart from those 15 studies that fulfilled eligibility criteria for development and testing of algorithms, we identified one randomized controlled trial [1] and one cost-effectiveness study [27].…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The automated diagnosis appeared to influence the decision-making of the physicians, but overdiagnosis of STEMI by the automated ECG analysis, which was detected by a simple algorithm, was reported, with a false-positive rate up to 42% with acute pericarditis as one of the leading causes [ 12 , 13 , 14 ]. As artificial intelligence (AI) techniques rapidly evolved, several deep learning models (DLMs) were developed and shown to achieve the performance of human experts in detecting numerous cardiac diseases [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Several AI-based algorithms have been used to detect STEMI; however, to the best of our knowledge, there is no study regarding the application of AI to recognize acute pericarditis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%